PENGUATAN KARAKTER RELIGIUS MELALUI PEMBIASAAN MEMBACA ASMAUL HUSNA PADA PEMBELAJARAN PAI DI SDN 2 KARANGGONDANG - Mardaningsih, Esa; Rohman, Fathur (Universitas Yudharta Pasuruan, 2024)
This article aims to analyze strengthening of religious character through the habituation of reading Asmaul Husna. This article is the result of field research at SDN 2 Karanggondaang. This research conducted with a qualitative approach with a qualitative descriptive method. The data collection was carried out by observation of the habituation activities of reading Asmaul Husna at the beginning of PAI learning. reading Asmaul Husna at the beginning of PAI learning, interviews with the principal, PAI teacher, students and documentation of the excavation of data. principal, PAI teacher, students and documentation of the excavation of institutional documents and activities. institutional documents and activities. The data analysis technique was carried out data reduction, data presentation, and conclusion drawing. Research results The results showed that through the habituation of Asmaul Husna can be one of the means to improve religious character that includes the character of obedience means to improve religious character which includes the character of obedience, discipline, sincerity, tolerance, politeness and responsibility.